2022
DOI: 10.1108/k-12-2021-1328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual perceived dissimilarity on social media fatigue: the mediating role of social anxiety

Abstract: PurposeThe increasing social media use has been widely recognized for its adverse effects, such as social media fatigue. With the continuously increasing friends on social media, the dissimilarity of individuals in terms of age, personality, and values has increased. It is unclear whether perceived dissimilarity with others is associated with social media fatigue. The authors attempted to bridge this gap by constructing a “perception–emotion–behavioral” research framework. This study investigated the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…(Zhang and Han, 2022) There is a consensus in the academic community that the state of people is more relaxed and authentic due to the strong anonymity of weakly connected social media and the invisibility of class and economic status among users. (Yang and Zhang, 2023) Therefore, hypothesis H4 is proposed: Social media connection, as the basis of the internal working model of social media attachment, exerts indirect effects on college students' subjective well-being by influencing self-presentation, information acquisition and selfesteem on social media.…”
Section: The Relationship Between Social Media and Subjective Well-beingmentioning
confidence: 99%
“…(Zhang and Han, 2022) There is a consensus in the academic community that the state of people is more relaxed and authentic due to the strong anonymity of weakly connected social media and the invisibility of class and economic status among users. (Yang and Zhang, 2023) Therefore, hypothesis H4 is proposed: Social media connection, as the basis of the internal working model of social media attachment, exerts indirect effects on college students' subjective well-being by influencing self-presentation, information acquisition and selfesteem on social media.…”
Section: The Relationship Between Social Media and Subjective Well-beingmentioning
confidence: 99%
“…Earlier researchers reported that individuals’ widespread use of social media has both a bright side and a dark side (Ali et al , 2023; Gao et al , 2018; Gong et al , 2020; Lin et al , 2023; Shan et al , 2021; Yang et al , 2022). The bright side is seen in terms of building social capital and psychological well-being (Zhang and Jung, 2022), perceived social support and decreased loneliness (Choi and Noh, 2020; Gerke et al , 2020; Zhang et al , 2021), life satisfaction (Raza et al , 2020a) and happiness (Chae, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technological revolution, followed by the growth of the internet and the availability of mobile devices, has resulted in the rapidly increasing use of social media worldwide (Gong et al , 2020; Nikolinakou and Phua, 2023; Yang et al , 2022). While social media use is quite common among individuals, the use of social media by students in academic settings has received little attention by academic scholars.…”
Section: Introductionmentioning
confidence: 99%